Antibiotic resistance: a geopolitical issue. (October 2014) - Carlet, J.; Pulcini, C.; Piddock, L. J. V.
Abstract Antimicrobial resistance (AMR), associated with a lack of new antibiotics, is a major threat. Some countries have been able to contain resistance, but in most countries the numbers of antibiotic‐resistant bacteria continue to increase, along with antibiotic consumption by humans and animals. AMR is a global issue, and concerns all decision‐makers worldwide. Some initiatives have been undertaken in the last 15 years, in particular by the WHO, the European Centre for Disease Prevention and Control, and the CDC, but those initiatives were partial and poorly implemented, without coordination. Very recently, some important initiatives have been implemented by the WHO. Since 2009, a US and European joint task force, the Trans‐Atlantic Task Force on Antibiotic Resistance, has been working on common recommendations. At a national level, some important initiatives have been implemented, in particular in European countries and in the USA. The Chennai declaration, in India, is also a good example of a multidisciplinary and national initiative that was highly political. Finally, several non‐governmental non‐profit organizations are also very active, and have helped to raise awareness about the problem of AMR. In the future, this global issue will need political involvement and strong cooperation between countries and between international agencies.